Hubungan Kekuatan Otot Tungkai Terhadap Hasil Lompat Jauh Pada Siswa / Siswi Kelas VIII Di SMP N 22 Kota Bengkulu - Majid, I. Abdul; Sumantri, Ajis; Perdima, Feby Elra (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine the relationship between leg muscle strength and long jump results in students of class VII.2 at SMP N 22 Bengkulu City. This research method is quantitative description research. The sample in this study based on these criteria amounted to 32 students. The results of hypothesis testing tests that leg muscle strength that there is a significant relationship between leg muscle explosiveness on long jump results. With this significant relationship can be seen based on the test results Significant correlation coefficient (thitung = 7,72129107>ttabel = 2,04227) Based on the correlation significance test The relationship between leg muscles (X) to the results of the long jump (Y) as seen in the table above obtained thitung = 7,72129107>ttabel = 2,04227 at a significant level α = 0.05 divided by 2 because it has 2 variables so that the significance level is α = 0.025. Thus Ha which says there is a relationship between leg muscle strength (X) and long jump results (Y) in students of class VII.2 is accepted, consequently Ho is rejected. This finding concludes that there is a relationship between leg muscle strength and long jump results in students of class VII.2 at SMP N 22 Bengkulu City.